Using Chain Writing Method to Improve the Students' Skills in Writing Descriptive Texts - Annida Nur Cahyaningtyas; Slamet Riyadi; Mustasyfa Thabib Kariadi (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2024)
Chain writing is an active and fun learning by doing activities which enable the students to negotiate and allow them to express their ideas to certain topics with their classmates. This research aimed to (1) to figure out the implementation of chain writing method to the students’ writing skill, (2) to prove whether or not the chain writing method improves the students’ writing skill, and (3) to reveal that the students’ responses to the implementation of chain writing method on students’ writing skill. This research uses a quantitative experimental design. The subjects of this research were the seventh-grade students of SMP Muhammadiyah 1 Purwokerto with the research samples of two classes (Grade 7C as control class and Grade 7D as experimental class. The research data were collected though observation, tests, and questionnaire. The results showed that (1) the implementation of chain writing method was successful as the teaching and learning processes conducted using chain writing method had no serious problems, the teacher give a clear explanation on the use of chain writing method, and the students well understood the explanations on the use of chain writing method. 2) the use of chain writing method improved the students’ ability in writing a descriptive text proven by the students’ test results from the pre-test and post-test scores increasing from the mean of pre-test score (40 points from the total score of 1.328) and that of post-test score (70 points from the total score of 1.891). 3) The students gave positive response to the chain writing method proven by 81% of students gave positive response on 8 question items in the research questionnaire. Thus, it can be concluded that chain writing method improved the students’ skills in writing descriptive texts. Keywords: Chain Writing, Descriptive Text, Experimental Study